Indoor localization system based on UWB sensors to determine the change of path - Suresh, Mahalakshmi (2019)
Indoor positioning is currently gaining attention as sensing the positions indoors requires high precision and it is quite challenging as objects deflect signals. Many techniques for indoor positioning have been devised but still reliable positioning is difficult to achieve. UWB is an emerging technique that has shown high performance compared to other techniques. Both narrow and wide-band systems are used for short-range positioning using UWB. UWB is proven to be an effective Indoor Positioning Technique where it produces promising results. The mechanism of the entire system with its hardware documentation is explained. The time difference of arrival technique is utilized for position estimation. Experimental results of the Indoor Positioning Systems are also provided. This dissertation provides the estimation of number of users present indoors, their duration of presence indoors, detecting the change of path movement of the users and finally classifying the data using Machine Learning Algorithms. The dissertation presents the comparison of classification algorithms in terms of predicted accuracy, root means square error, and error rate. Secondly, methods for estimating positions using UWB are discussed, and in addition there are discussions about the DW1000 UWB Transceivers and its key features are stated. The dissertation finally shows practical Real Time Location Systems and its implementation in an indoor environment. Finally, the thesis showcases the overview of the Indoor Positioning Systems, its various positioning techniques, the different positioning algorithms and implementations of the UWB Indoor Positioning Systems which will keep all researchers and practitioners up-to-date of the recent developments.